24-h-ambulatory blood pressure monitoring in sub-Saharan Africa: hypertension phenotypes and dipping patterns in Malawian HIV+ patients on antiretroviral therapy - Kasper, Philipp Maria; Nhlema, Angellina; De Forest, Andrew; Tweya, Hannock; Chaweza, Thom; Mwagomba, Beatrice Matanje; Mula, Adam M.; Chiwoko, Jane; Neuhann, Florian; Phiri, Sam; Steffen, Hans-Michael (Global heart, 2021)
Article: 24-h-Ambulatory Blood Pressure Monitoring in Sub-Saharan Africa: Hypertension Phenotypes and Dipping Patterns in Malawian HIV+ Patients on Antiretroviral Therapy
Gesehen am 15.01.2022